The detection and phylogenetic analysis of Anaplasma phagocytophilum-like 1, A. ovis and A. capra in sheep: A. capra divides into two genogroups - Altay, Kursat; Erol, Ufuk; Sahin, Omer Faruk; Aytmirzakizi, Ayperi; Temizel, Ethem Mutlu; Aydin, Mehmet Fatih; Aktas, Munir (Springer, 2022)
In this study, the presence, prevalence, and genotypes of Anaplasma phagocytophilum, A. ovis, and A. capra in sheep were investigated based on 16 S SSU rRNA, groEL, and gtlA gene-specific polymerase chain reaction (PCR), respectively. The sequences of the genes were used for detection of the phylogenetic position of the species. Additionally, a restriction fragment length polymorphism (RFLP) were carried out for discrimination of A. phagocytophilum and related variants (A. phagocytophilum-like 1 and 2). The prevalence of Anaplasma spp. was found as 25.8% (101/391), while it was found that A. ovis, A. phagocytophilum-like 1, and A. capra are circulating in the sheep herds in Kyrgyzstan, according to the PCRs, RFLP and the partial DNA sequencing results. The positivity rates of A. phagocytophilum-like 1, A. ovis, and A. capra genotype-1 were 6.9, 22.5, and 5.3%, respectively. A total of 32 (8.2%) sheep were found to be mix infected. Moreover, phylogenetic analyses and sequence comparison with those available in the GenBank showed that A. capra formed two distinct genetic groups (A. capra genotype-1 and A. capra genotype-2). Considering the zoonotic potential of these species, it may be necessary to make changes in the interpretation of anaplasmosis cases in animals and there is a need for further studies to determine the pathogenicity of the species/genotypes circulating in animals.
Keywords: Anaplasma species; Anaplasma capra genotypes; 16S SSU rRNA; groEL; gtlA; Sheep